IMPLEMENTASI CORE VALUE 'GANESHA CEPAT' UNTUK PENINGKATAN KINERJA DOSEN DAN TENAGA KEPENDIDIKAN - Ramadani Pardian; Ahmad Fadli; Zubair Arza; Nurhayati; Nurmayani Istiningsih (JURNAL LENTERA BISNIS, 2025)
This study aims to explore the understanding and implementation of the core value "Ganesha CEPAT" at STIE Ganesha, as well as the challenges faced in its application. Using a qualitative approach with a case study method, this research involved 15 participants comprising lecturers from three study programs (Master's in Management, Bachelor's in Management, and Bachelor's in Accounting) and administrative staff from the administration, student services, and finance departments. Data were collected through in-depth interviews, direct observations, and institutional document analysis. The findings indicate that the majority of participants understand the importance of core values in building a positive work culture, although challenges such as variations in understanding and inconsistencies in implementation were identified. Thematic analysis was used to identify key patterns in the data, while triangulation ensured the validity and reliability of the findings. This study reveals that the implementation of the core value "Ganesha CEPAT" can enhance the performance of lecturers and administrative staff if supported by consistent socialization programs and adequate managerial support. The implications emphasize the importance of developing a value-based work culture in higher education institutions to improve effectiveness and sustainability.